6th International Conference On Quran As Foundation Of Civilization (SWAT) 2019 - Nurulwahidah Fauzi; Samer Najeh Abdullah Samarh; Mesbahul Hoque; Tazul Islam (Universiti Sains Islam Malaysia, 2024)
Paper proceedings, Hosted By : Faculty Of Quranic And Sunnah Studies Universiti Sains Islam Malaysia (USIM)